The evolving role of checkpoint inhibitors in the treatment of Hodgkin lymphoma - Cashen, Amanda F. (Frontiers in Oncology, 2024)
Since their initial approval as single agent therapy for multiply relapsed/refractory Hodgkin lymphoma (HL), the PD-1 inhibitors nivolumab and pembrolizumab have been incorporated into second-line salvage regimens, and they are being investigated in upfront therapy of newly diagnosed patients. As second-line therapy in combination with brentuximab vedotin or multi-agent chemotherapy, nivolumab and pembrolizumab provide high complete remission rates and durable progression-free survival after consolidative autologous stem cell transplant. Incorporation of these agents into frontline chemotherapy regimens is feasible, and early results from a Phase III trial of nivolumab-AVD compare favorably with the existing standard for advanced stage HL, brentuximab vedotin plus AVD. As nivolumab and pembrolizumab move into earlier lines of HL therapy, open research questions include the efficacy of checkpoint inhibitor regimens in patients who relapse after frontline exposure to nivolumab or pembrolizumab; the selection of patients with relapsed HL who can achieve durable remissions without autologous stem cell transplant; and the efficacy of the PD-1 inhibitors in the frontline therapy of patients with early stage Hodgkin lymphoma.